Structural and Mechanical Properties of Lignite Fly Ash and Flax-added Polypropylene Polymer Matrix Composite. Issue 13 (1st December 2022) - Rajkumar, G.; Sathishkumar, G.K.; Srinivasan, K.; Karpagam, R.; Dhivya, V.; Sakthipandi, K.; Sivakumar, R.; Ibrahim, Mohamed; Mohamed Akheel, M.
ABSTRACT: Flax fiber-containing polypropylene-based polymer matrix composites (PMCs) with different lignite fly ash (LFA) contents were synthesized using the formula (80 − x) PP − 20 F – x LFA (where x = 0, 2.5, 5.0, 7.5, and 10.0 wt.%) and analyzed. The added LFA acted as a filler material in the polymer network to re-formulate the microstructure of PMCs. The structural changes in the PMCs were induced to alter their thermal stability and mechanical strength. A linear increase in T g, density, and compressive strength values was observed up to addition of 10 wt.% LFA in the prepared PMCs. Fourier transform infrared spectra revealed the structural changes that occurred in the polymer network for all the samples during the addition of LFA. Results of the X-ray diffraction studies confirmed the crystalline phase of the added LFA in the PMCs. Contact angle and surface energy studies showed a higher contact angle and lower surface energy in the PMC sample containing 5 wt.% LFA. The low wear depth in the sample containing 5 wt.% LFA confirmed its better wear than other samples. The obtained results confirmed that the flax fiber-added polypropylene composite with 5 wt.% LFA is suitable for aerospace, construction, and automobile applications.